2008
DOI: 10.1016/j.juro.2008.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Ureteroneocystostomy and Psoas Hitch for Post-Hysterectomy Ureterovaginal Fistula

Abstract: Laparoscopic ureteroneocystostomy with a psoas hitch for ureterovaginal fistula secondary to hysterectomy is safe and effective, and associated with a low incidence of postoperative reflux and obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 19 publications
0
24
0
8
Order By: Relevance
“…Laparoscopic extravesical Lich-Gregoir ureteroneocystostomy has a success rate of 90-100% [19]. Successful outcomes were also reported with this technique in lower ureteric strictures from our institute [20].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Laparoscopic extravesical Lich-Gregoir ureteroneocystostomy has a success rate of 90-100% [19]. Successful outcomes were also reported with this technique in lower ureteric strictures from our institute [20].…”
Section: Discussionmentioning
confidence: 97%
“…It also gives an additional length of lower ureter for non-refluxing anastomosis and also the angulation at anastomosis doesn't change irrespective of the filling state of the bladder. Non-refluxing anastomosis was advocated because this condition was found in the age group of those who were sexually active and were predisposed to recurrent UTI [19]. …”
Section: Discussionmentioning
confidence: 99%
“…It can be performed by extra or intra-vesical technique using Politano-Leadbetter, Lich-Gregoir, the Boari technique (Boari's flap) or psoas-hitch technique in cases of major stenoses. In the literature, the performance of reimplant with the Boari or psoas-hitch technique is described with favorable results and low occurrence of reflux (7)(8)(9). In these cases, the laparoscopic access offers advantages such as mobilization of the bladder, ureter and kidney, making the anastomosis easier and without tension and/or adequate size of the vesical flap.…”
Section: Commentsmentioning
confidence: 99%
“…Selzman et al observed an 11% stricture rate after 1 year following open ureteral reimplantations for ureteral injury (23). The median follow-up time was 35 months, which represents one of the longest for a laparoscopic ureteral reimplantation series (9,24). The results are comparable to open surgery with the advantages of a minimally invasive procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopy provides patients the advantages of quicker recovery, low postoperative morbidity, less postoperative pain, less blood loss and better cosmesis (7,8). Successful results using laparoscopic ureteral reimplantations have been reported in the literature to treat ureteral strictures, iatrogenic injuries, VUR, and ureterovaginal fistulas (8,9). It demonstrates that laparoscopic ureteral reimplantation has comparable functional outcomes to open surgery (8).…”
Section: Introductionmentioning
confidence: 99%